PERBEDAAN HASIL BELAJAR SISWA KELAS X SMA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING (SFE) DAN MODEL PEMBELAJARAN KONVENSIONAL PADA MATERI TRIGONOMETRI - Ruhulessin, Stela; Ratumanan, Tanwey Gerson; Tamalene, Hanisa (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2019)
This study aims to determine whether there are differences in learning outcomes of class X students of SMA 12 Ambon using cooperative learning model Student Facilitator and Explaining (SFE) and conventional learning models on trigonometric material. The type of research is experimental research (Experimental Research) with the Post-Test Only Control Group Design. The analysis technique is descriptive statistical analysis and inferential test statistics consisting of normality test data, homogeneity test and hypothesis test. The data are processed using SPSS version 20.0. The results of this study are (1) there are differences in learning outcomes using the cooperative learning model Student Facilitator and Explaining and conventional learning models, which shows that the value of t_hitung 3.1128 is greater than the value of t_tabel 2.0003 and the value of Sig. (2-tailed) smaller than the value of alpha 0.05 which is 0.002; (2) learning outcomes of students who use the cooperative learning model Student Facilitator and Explaining type are better when compared to those using conventional learning models